TWO-SIDED WAVE GENERATION IN A HIGH-ORDER SPECTRAL NUMERICAL WAVE TANK - Aertsens, Tim; Ducrozet, Guillaume; Toffoli, Alessandro; Monbaliu, Jaak (AMER SOC MECHANICAL ENGINEERS, 2023)
sponsorship: This research is part of a PhD project funded by the Research Foundation -Flanders (FWO), with project number 1S36822N. This work was also partly supported by the WASANO project, funded by the French National Research Agency (ANR) as part of the "Investissements d'Avenir" Programme (ANR-16-IDEX-0007). The construction of the physical COB is made possible by funding from the Hercules Foundation and the Government of Flanders. T.A. thanks Louis Voets for collaborations. (Research Foundation -Flanders (FWO)|1S36822N, WASANO project - French National Research Agency (ANR)|ANR-16-IDEX-0007, Hercules Foundation, Government of Flanders) status: Published